2016
DOI: 10.3389/fnsyn.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of Functionally Different Vesicular Neurotransmitter Transporters

Abstract: The vesicular transmitter transporters VGLUT, VGAT, VMAT2 and VAChT, define phenotype and physiological properties of neuronal subtypes. VGLUTs concentrate the excitatory amino acid glutamate, VGAT the inhibitory amino acid GABA, VMAT2 monoamines, and VAChT acetylcholine (ACh) into synaptic vesicle (SV). Following membrane depolarization SV release their content into the synaptic cleft. A strict segregation of vesicular transporters is mandatory for the precise functioning of synaptic communication and of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 81 publications
(108 reference statements)
0
18
0
Order By: Relevance
“…Nine out of ten cells expressed either VGLUT1 or VGLUT2, or both (Figure 1C ). The presence of these transporters is indicative of an excitatory, glutamatergic phenotype, as VGLUT is required to load synaptic vesicles with glutamate (Münster-Wandowski et al, 2016 ). Interestingly, we also found that some of these cells expressed mRNA for the markers GAD65, GAD67, PARV, SOM, and vasoactive intestintal peptide (VIP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine out of ten cells expressed either VGLUT1 or VGLUT2, or both (Figure 1C ). The presence of these transporters is indicative of an excitatory, glutamatergic phenotype, as VGLUT is required to load synaptic vesicles with glutamate (Münster-Wandowski et al, 2016 ). Interestingly, we also found that some of these cells expressed mRNA for the markers GAD65, GAD67, PARV, SOM, and vasoactive intestintal peptide (VIP).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our observations indicate significant molecular diversity among the pyramidal cell population of the mPFC. The co-expression of VGLUT and GAD in mPFC PN is likely important for proper execution of mPFC function (Münster-Wandowski et al, 2016 ). It is possible that the diverse pyramidal subtypes subserve different components of the behaviors we have assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal activity presents a substantial challenge to local acid-base balance. Neurotransmitter-filled vesicles release H + into the synaptic cleft [92] , [93] (H + themselves may be considered to be neurotransmitters [94] ) and are removed from the synaptic cleft by H + -coupled neurotransmitter transporters such as the excitatory amino acid transporter EAAT1. GABA-activated anion channels in neurons and astrocytes release HCO 3 – [95] , [96] , and the Ca 2+ /H + exchange activity of the plasma membrane Ca 2+ -ATPase (PMCA) in neurons causes a rise in extracellular pH as it restores intracellular Ca 2+ following an action potential [97] .…”
Section: Applications By Organ Systemmentioning
confidence: 99%
“…Vesicular glutamate transporters are comprised of three homologous proteins (VLUT1-3) localized to functionally distinct populations of glutamatergic neurons [46]. VGLUTs utilize a proton electrochemical gradient to carry glutamate into synaptic vesicles, and the efficiency of this inward transport is maximized by low concentrations of the chloride anion [47].…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%